Loss of innocence : America's scandals in the post-war years - Matthews, Melvin E. (Algora Publishing, 2019)
"Loss of Innocence explores the sunny, innocent mood of post-War America and the budding skepticism that began to creep into the minds of an overly-credulous public in the 1950s. Taking the quiz show scandals of the 1950s and the U-2 spy incident of 1960 as examples, the book argues that these two events shook the public and began to erode their blind faith in government and institutions, creating a credibility gap that haunts us to this day"--